FOOD CONSUMPTİON PREFERENCES OF INDİVİDUALS AGED OVER 45 YEARS OLD (Third Sector Social Economic Review, 2011)
This research has been planned and conducted in order to determine nutrition habits, food consumption preferences and the factors effecting these preferences of individuals aged over 45 years old who live in the city of Kilis. Data have been collected from 140 participants by means of a questionnaire. The age of the 64.3 % of the participants is between 45-64, the age of the rest (35.7 %) is 65 and over. 53.6 % of the participants is literate or graduates of primary school. 19.3 % of the individulas do not have any health problems. The health problems encountered frequently by the rest of the participants are: Hypertension, rheumatism, joint complaints, gynecological diseases and stomach sicknesses. It has been detected that 67.0 % of the participants were taking medicene on a regular basis. It has been identified that 40.5 % of the participants aged between 45-64 and 59.5 % of the participants aged over 65 were skipping one meal (p
Keywords: Food comsumption preference; food consumption frequency; nutritional habit